Knowledge, awareness, and attitudes toward hemorrhoids and related surgical treatments among the general population in the Western region, Saudi Arabia: a cross-sectional study - Al Sawat, Abdullah; Althobaiti, Hanan S.; Almukhlifi, Ayman S.; Alkhmis, Zainab B.; Alqarni, Mohammed M.; Aljohani, Ammar M.; Alhazmi, Emad S.; Aljohani, Saleh S. (International Surgery Journal, 2024)
Background: Hemorrhoids, or swollen veins in the anal canal, can result from factors such as chronic straining during bowel movements. While categorized as internal or external, they typically manifest as painless rectal bleeding, swelling, or a lump. Despite their significant global prevalence and impact, research on hemorrhoids in Saudi Arabia remains limited. This cross-sectional study aimed to evaluate public knowledge and attitudes toward hemorrhoids, anticipating prevalent misconceptions. Methods: It is a cross-sectional study conducted in the Western region of Saudi Arabia. Self-administered questionnaires will assess demographic data and perceptions about hemorrhoids. Data is analyzed by IBM SPSS 29. Results: Our study indicated that 97.7% were aware of hemorrhoids, with 18.9% citing pushing during excretion and 16.4% mentioning prolonged sitting as the leading cause. 30.1% perceived surgery as the primary treatment, and 85.9% agreed on hemorrhoids’ negative impact on quality of life. Significant predictors of better knowledge included (OR=1.726) for the 21-40 age group, (OR=2.024) for Taif residents, (OR=3.393) for Ph. D. holders, (OR=1.567) for an income of 5000-10000 SAR, and (OR=8.542) for participants with prior knowledge of hemorrhoids. Conclusions: Our study sheds light on the knowledge, attitudes, and perceptions about hemorrhoids among the general population in the Western region of Saudi Arabia. There is good awareness but inadequate knowledge regarding hemorrhoids and their surgical treatment in the Western region of Saudi Arabia. The findings underscore the need for targeted educational interventions.